A gastric and pleural metastasis of occult breast lobular cancer in an elderly female and radiomics assisted analysis of a rare metastasis - Xie, Yuxin; Gou, Qitao; Wu, Wenjun; Zhao, Shuang; Yang, Libo; Gou, Qiheng (Frontiers in Oncology, 2026)
BackgroundMetastatic breast cancer involving the gastrointestinal tract is rare, particularly in lobular carcinoma, often emerging later in disease progression. Occult primary breast tumors are exceptionally uncommon. This study reports the first case of occult breast lobular carcinoma (OBLC) with concurrent gastric and pleural metastases in a 65-year-old female.MethodsA multidisciplinary diagnostic approach integrated histopathological and radiomic analyses. Immunohistochemical (IHC) profiles of axillary lymph node and gastric lesions were compared. Chest enhanced computed tomography (CT)-based radiomics quantified tumor texture features across five time points (T1-T5: pre- and post-treatment). The patient received aromatase inhibitors (AIs) combined with CDK4/6i as first-line treatment and chemotherapy as second-line treatment.ResultsImmunohistochemistry confirmed consistent biomarker expression across metastatic sites, including ER positive, PR negative, HER2 negative and GATA3 positive. However, S100, SALL4, Syn, CDX2 and CgA were all expressed negatively in gastric metastatic lesions. Radiomics revealed progressive tumor brightness peaking at T3 (pre-treatment), followed by significant attenuation post-treatment (T4-T5). The ngtdm_Strength parameter increased markedly at T4-T5, compared to T1-T3, reflecting altered tumor vascularity after therapy. After two lines of treatment, the patient has survived for 24 months.ConclusionsThis case highlights OBLC’s diagnostic complexity and underscores the role of radiomics in tracking metastatic evolution. Coordinated IHC and CT-based texture analysis aided lesion characterization and treatment monitoring for managing gastric metastases in OBLC.